The Impact of Frozen Storage Duration on Physicochemical Properties and Antioxidant Content in Taliwang Chicken Dishes - Bulkaini, Bulkaini; Kisworo, Djoko; Fahrullah, Fahrullah; Wulandani, Baiq Rani Dewi; Jupri, Ahmad; Bidura, I Gusti Nyoman Gde (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Taliwang Chicken is a typical dish that has been popular on Lombok Island since the time of the Selaparang Kingdom. The research was conducted with the aim of determining the Effect of Frozen Storage Duration at −20°C on the Physicochemical Characteristics and Antioxidant Levels of Taliwang Chicken Dishes. The research materials included 12 Balitbangtan village chickens (6 weeks old), spices for Taliwang Chicken Dishes, and chemicals for testing composition and antioxidant levels. The study used an experimental method with a completely randomized design (CRD) in a one-way pattern to test storage at -20°C. Three storage treatments (P1: 2 days, P2: 4 days, P3: 6 days) were tested, each with 3 replications. The measured variables were: (1) pH, measured with a digital pH meter; (2) water binding capacity by the pressing method; (3) chemical composition (moisture, protein, fat) by proximate analysis; and (4) antioxidant levels by the DPPH method. Data were analyzed with ANOVA and, if needed, the Duncan Multiple Range Test in SPSS 25. One-way ANOVA showed storage time at -20°C had a very significant effect (P<0.01) on fat and water content, but not on protein content, pH, cooking loss, water holding capacity (WHC), or antioxidants (P>0.05). Conclusion: Storing Taliwang Chicken Dishes for 6 days at -20°C maintains quality in nutritional value, physical properties, and antioxidant levels.